Tailored Practical Management of Patients With Atrial Fibrillation: A Risk Factor-Based Approach - Pastori, Daniele; Menichelli, Danilo; Gingis, Rony; Pignatelli, Pasquale; Violi, Francesco (Frontiers in Cardiovascular Medicine, 2019)
The management of antithrombotic therapy for thromboprophylaxis in patients with atrial fibrillation (AF) has been recently evolved by the progressive replacement of vitamin K antagonists with the non-vitamin K antagonist oral anticoagulants (NOACs). However, while these drugs are effective in reducing ischemic stroke/systemic embolism, a still high rate of cardiovascular events is present in the AF population. A tailored integrated approach to patients with AF is therefore necessary to reduce both thromboembolic events and cardiovascular disease. This approach should consist in the assessment of individual risk factors for ischemic and bleeding events in order to choose the most appropriate anticoagulant treatment according to patient's characteristics and preference. To this purpose, several risk scores have been developed and validated to stratify thromboembolic and hemorrhagic risk. This review provides an individual-based strategy for the management of patients with AF, from a risk-factor based approach to a tailored prescription and monitoring of NOACs. In particular, we reported an updated practical management strategy for AF patients in specific clinical situations such as those (1) experiencing a major bleeding, (2) requiring a switch to another antithrombotic regimen, (3) restarting anticoagulation after acute ischemic stroke, (4) suffering from an acute coronary artery disease (acute coronary syndrome or undergoing cardiac revascularization).